Modern Trends of Engineering Pedagogy Development - T. Y. Polyakova (Moscow Polytechnic University, 2019)
The article is devoted to modern trends of engineering pedagogy development that are global due to the processes of globalization and internationalization of higher technical education. The tendencies of engineering pedagogy development as a pedagogical science are connected with the key pedagogy concepts of teaching aims, content, forms, technologies, and aids. The trends of development are determined by the necessity to overcome the contradiction between fast changes in the sphere of engineering activities and certain conservatism, lag effect typical for engineering education system. At present, there are several general trends. Fast changes of modern society require regular analysis of social needs, specification and updating of engineering education aims, which takes place in the conditions of changeability and uncertainty and are more and more based on prediction. New forms of engineers' training appear in order to overcome the gap between the requirements of engineers' activities and the results of their education, and they are organized by joint efforts of universities, researchers, industry and business. New technologies of education involving the latest achievements in science, techniques and technologies are being developed and introduced in the educational process. Regular changes in educational process make the engineering education system to some extent unstable and unbalanced, and this trend may be expected to intensify. In order to correspond to the situation and to develop new technical teachers' competences, various specialized diversified courses are offered to meet specific requirements of particular target groups.